Discrepancy in Vancomycin AUC/MIC Ratio Targeted Attainment Based upon the Susceptibility Testing in Staphylococcus aureus - Seenae Eum; Robert L. Bergsbaken; Craig L. Harvey; J. Bryan Warren; John C. Rotschafer (MDPI AG, 2016)
This study demonstrated a statistically significant difference in vancomycin minimum inhibitory concentration (MIC) for Staphylococcus aureus between a common automated system (Vitek 2) and the E-test method in patients with S. aureus bloodstream infections. At an area under the serum concentration time curve (AUC) threshold of 400 mg∙h/L, we would have reached the current Infectious Diseases Society of America (IDSA)/American Society of Health System Pharmacists (ASHP)/Society of Infectious Diseases Pharmacists (SIDP) guideline suggested AUC/MIC target in almost 100% of patients while using the Vitek 2 MIC data; however, we could only generate 40% target attainment while using E-test MIC data (p < 0.0001). An AUC of 450 mg∙h/L or greater was required to achieve 100% target attainment using either Vitek 2 or E-test MIC results.